Using sequence analysis to explore the group interaction within a Circle of Adults: an exploratory study - Connor, Lauren, Jade (2018)
Educational settings are required to differentiate for students with special educational needs which may now include social, emotional and mental health difficulties (SEND Code of Practice, 2014). Educational psychologists are often called upon by schools to support them in meeting the needs of vulnerable children. When aiming to build capacity in schools and facilitate change, educational psychologists increasingly opt to use consultative methods (Ingraham, 2000). Circle of Adults is a tool used by educational psychologists to facilitate group problem solving (Grahamslaw and Henson, 2015). Yet despite its growing popularity, little is known about what yields successful outcomes (Bennett and Monsen, 2011). To understand the efficacy of the intervention, psychological theories of group interaction have been consulted. Though there is a consensus that groups interact in predictable ways (Wheelan, 1994), there are contrasting explanations for what actually happens within groups. Thus, the group dynamics within a Circle of Adults are not yet fully understood. This research aimed to enhance the existing evidence base by exploring the interactional patterns occurring within the group during Circle of Adults. Five Circle of Adults were observed and coded using Bales’ Interaction Process Analysis (IPA, 1951). Sequence analysis showed that 27 first order event pairs were found, indicating that Circle of Adults facilitates predictable group interaction. Findings also demonstrated that the intervention enables discussion which is functional in nature and that within the group, there is a balance between task and emotional interactional processes occurring. Implications of this research are considered, particularly focusing upon how this research can be used by educational psychologists and local educational authorities. Through critically considering the methodology used, recommendations for future research are made.